2010
DOI: 10.1097/bsd.0b013e318198cd4d
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic Surgical Treatment for Centrally Located Thoracic Disc Herniations Presenting With Myelopathy

Abstract: Thoracotomy for treatment of centrally located thoracic disc herniations is associated with improvement in or stabilization of myelopathic symptoms in the majority of patients with an acceptable rate of complications. Interestingly, most patients with weakness improved in strength (12/16, 75%), no patients with normal strength developed new weakness (10/10, 100%), and only 2 patients had new weakness noted postoperatively (7.4%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 26 publications
2
49
0
4
Order By: Relevance
“…Martín et al 5 found an incidence of 11.3%. As for the thoracic level, Ayhan et al 4 noted worsening on the ASIA scale of 7.4% of the patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Martín et al 5 found an incidence of 11.3%. As for the thoracic level, Ayhan et al 4 noted worsening on the ASIA scale of 7.4% of the patients.…”
Section: Discussionmentioning
confidence: 98%
“…2 In literature, there are series of isolated cases, although very few general reviews covering the various etiologies of iatrogenia in SCI, which focus especially in surgical treatment. The causes found are the following: Surgical: laminectomy, 3 discectomy, 4 arthrodesis, 5,6 scoliosis, 7 exeresis of calcified yellow ligaments, 8 vascular surgery, 9,10 use of surgicel. 11,12 Interventionist techniques: vertebroplasty, 13 arterial embolization, 14 epidural anesthesia, 15 intramuscular injections, 16 acupuncture.…”
Section: Introductionmentioning
confidence: 99%
“…18 The anterior open transthoracic approach provides optimal ventral exposure and has been recommended. 7,8,10,18,19 The use of a microscope to remove the calcified herniated disc under direct vision was safe and resulted in limited bone excision and thus avoided the need for fusion surgery. The use of an endoscope or microscope in a minimally invasive procedure has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Surgical treatment for calcified thoracic disc herniation is challenging. [6][7][8][9][10] Calcified lesions are often voluminous and adherent to the ventral dura mater. Despite development of numerous techniques, appropriate surgical procedures remain controversial.…”
mentioning
confidence: 99%
See 1 more Smart Citation